M'bona The Black Jesus of Malawi - Chikabadwa, Eva (Michaelis School of Fine Art, 2023)
This document is an explicatory essay for a body of artworks which are in the form of paintings and sculptures that tell the story of M'bona, the Black Jesus of Malawi. M'bona is a religious icon amongst the Man'ganja clan of Southern Malawi. He is believed to be a rain maker, a god and a prophet. Both the document and the artworks consider colonial and missionary interpretation and representation of M'bona and aspects of African religious practices. My focus on M'bona challenges representations of the faith by Catholic missionary anthropologist, Matthew Schoffeleers. The argument that I present is mainly developed from Schoffeleers' publications and academic documents, and from my field research at Khulubvi thicket in the Nsanje District of Malawi, which is the headquarters of the M'bona religion. The artwork installation expresses my response to the postulation made by Schoffeleers that the M'bona religion owes its genesis to an appropriation of Christian beliefs. The paintings, in particular, proffer my conceptual contest with Schoffeleers' suppositions, while the sculptures play the role of fortifying my alternative view point as one of the vital functions of art in the conservation of cultural heritage.